2005
DOI: 10.1080/00498250500087580
|View full text |Cite
|
Sign up to set email alerts
|

Structural identification of bitespiramycin metabolites in rat: A single oral dose study

Abstract: Bitespiramycin is a macrolide antibiotic consisting of a mixture of some nine spiramycin ester derivatives. It has a similar spectrum of antibiotic activity to that of spiramycin but has superior pharmacokinetic properties. In this study, a rapid and facile LC/ESI-MSn method was applied to study the metabolism of bitespiramycin in rat following a single oral dose (80 mg kg-1). Concentrations of parent drug constituents and metabolites were determined in plasma, urine, feces and bile. Concentrations of parent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Spiramycin has an oral bioavailability of ca. 35%, demonstrates low plasma protein binding (20%; which may explain the extensive tissue penetration), and is associated with hepatic to active metabolites (32). The elimination half-life (t 1/2 ) is around 6 to 8 h; spiramycin is excreted in bile and breast milk (13), and ca.…”
mentioning
confidence: 99%
“…Spiramycin has an oral bioavailability of ca. 35%, demonstrates low plasma protein binding (20%; which may explain the extensive tissue penetration), and is associated with hepatic to active metabolites (32). The elimination half-life (t 1/2 ) is around 6 to 8 h; spiramycin is excreted in bile and breast milk (13), and ca.…”
mentioning
confidence: 99%
“…All the other spectral data were consistent with the identification of UNK1 and UNK12 as deforosaminylspiramycin I and deforosaminylspiramycin III, respectively. These two compounds correspond to the metabolites of bitespiramycin found in rat after a single oral dose 22…”
Section: Resultsmentioning
confidence: 90%
“…Based on the results from these two publications,19, 20 it can be concluded that the fragmentation pathways of singly and doubly charged ions are in accordance. Degradation of spiramycins in acidic conditions and metabolism in rat and pig liver were also studied 17, 22, 23. In acidic conditions, SPM III produced two degradation products with m/z 755 (NSPM I) and 614 (forosidin III).…”
mentioning
confidence: 99%
“…Bitespiramycin, a mixture of 4''-O-acylated spiramycin with 4''-O-isovalerylspiramycin as the major components [1], belongs to 16-membered ring macrolide antibiotic [2] used to treat gram-positive bacteria infectious diseases in upper respiratory tract and urinary system [3][4][5].…”
Section: Introductionmentioning
confidence: 99%